Counseling on The Benefits of Virgin Coconut Oil on The Cure of Diaper Rush in Babies at Eka Sri Wahyuni Clinic - Husna Sari; Erlina Hayati; Stefani Anastasya Sitepu; Marlen Sadrina Sitepu; Tetty Junita Purba Junita Purba; Nur Mala Sari (INSTITUT KESEHATAN DELI HUSADA, 2023)
Infection, irritation and allergies are diseases that are prone to occur in infants due to the relatively thin layer of the baby's skin. diaper dermatitis/diaper rash is one of the most common skin problems in infants and children. Diaper rash occurs due to moisture in the baby caused by diapers that are too full of feces and urine. Virgin Coconut Oil is pure coconut oil that is processed without using high temperatures and the addition of chemicals. VCO contains saturated fatty acids and natural moisturizers contained in VCO absorb the inner layers of the skin and can help maintain skin flexibility and elasticity. The content of Lauric acid and capric acid in virgin coconut oil can kill viruses. This counseling activity aims to provide knowledge to mothers about virgin coconut oil which can be used for their baby's diaper rash. This community service is an educational process through counseling and training for mothers, especially teaching mothers how to make virgin coconut oil and informing them of the benefits contained in virgin coconut oil, as well as mothers knowing how to deal with diaper rash in non-pharmacological babies, namely by giving pure coconut oil (VCO).